Gambaran Kesiapan Anak Masuk Sekolah Dasar pada Siswa Kelas 1 SD Negeri Kecamatan Jabon - Febrianti, Aisyah Mawaddah; Mariyati, Lely Ika (ResearchJet Journal of Analysis and Inventions, 2024)
The research was conducted because of the phenomenon of the readiness of children to enter elementary school carried out by grade 1 elementary school students in the Jabon sub-district. The purpose of the study was to find out how the description of children's readiness to enter elementary school carried out by grade 1 elementary school students. The sample in this study amounted to 102 students from a total population of 110 students. This type of research is descriptive quantitative research. The variable in this study is the readiness of children to enter elementary school. The population in this study was 110 students. The sample in this study amounted to 102 students from a total population of 110. Sampling was carried out using a non-probability technique in the form of accidental sampling. Data analysis used descriptive analysis to find a picture of children's school readiness based on the value of the mode, mean, median, standard deviation, range of variance, and so on and then the data obtained was processed using the SPSS 17.0 for Windows program. Based on the results of the study, if the description of the readiness of children to enter elementary school in grade 1 students at SD Jabon Sidoarjo District, 85.3% (87 students) had high readiness to enter elementary school, 8.8% (9 students) had sufficient readiness to enter elementary school. 5.9% (6 students) are less ready to enter primary school.